Educational Animation Media on the Effects of Ultra-Processed Foods to Children's Cognitive Function: A Systematic Literature Review - Ramadhan Al - Aqil, Muhammad Reyhan; Agus Juhana (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2025)
The consumption of ultra-processed food (UPF) poses a serious risk of cognitive impairment to children during their critical brain development phase. Effective educational media is crucial, as animation is a highly engaging and proven medium for children, with 90% of them choosing animation for education in previous research. This study, therefore, aims to systematically review the topic by addressing three key research questions (RQs): (1) To what extent does UPF consumption affect children's cognitive function and health? (2) Why are animations the most effective media for transferring nutritional knowledge? (3) How effective is animation-based educational media in raising children's awareness regarding UPF risks? This study adopts a Systematic Literature Review (SLR) methodology, adhering to the PRISMA guidelines. The systematic literature search gathered scientific articles from reputable world libraries. The results confirm that UPF consumption is a significant factor contributing to cognitive decline and obesity due to its high sugar and low micronutrient content. Conversely, animation is proven effective as it significantly increases children's focus and comprehension. The core conclusion is that educational animation media serves as a strategic and highly effective tool for fostering children's awareness of the dangers of consuming UPF and promoting preventative behavior.